Proposal for a typology of self-employed considering the impact of the business and entrepreneurial engagement - Jéssica Borges de Carvalho; Cândido Borges (Regepe Entrepreneurship and Small Business Journal)
Aim of the study: to propose a typology of self-employed workers (self-employed), based on the dimensions of entrepreneurial impact and entrepreneurial engagement. Dilemma/problem or thesis: it is necessary to understand the different types of self-employed workers, since examining them as a single category could lead to limitations in the results of a study. Relevance/originality: as a criterion for defining the typologies, dichotomous categories were established to help with comparisons. The categories were: formalisation (formal or informal), innovation potential (with high innovation potential or low innovation potential), job creation (with an employee or without an employee), constancy in the activity as a TCP (intermittent or continuous), reconciliation of the activity with other professional/economic occupations (partial or full) and motivation (by opportunity or necessity). The dimensions adopted: impact of the enterprise and entrepreneurial engagement were considered to identify entrepreneurial activity and because they can be identified through actions. Four types of self-employed workers were proposed. Type 1 (innovator) has high impact and high engagement. Type 2 (explorer) has high impact and low engagement. Type 3 (conventional) has low impact and high engagement. Type 4 (temporary) has low impact and low engagement. Social contributions: the proposed typology is not about determining TCPs as being or not being entrepreneurs or assigning value judgements to the types, but about understanding their particularities and entrepreneurial activity, making it possible to choose and justify theories in the field of entrepreneurship and eventually direct appropriate actions and policies to each of the types.